2007
DOI: 10.1128/jvi.00724-07
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Mediated Interference with Influenza A Virus Polymerase

Abstract: The assembly of the polymerase complex of influenza A virus from the three viral polymerase subunits PB1, PB2, and PA is required for viral RNA synthesis. We show that peptides which specifically bind to the protein-protein interaction domains in the subunits responsible for complex formation interfere with polymerase complex assembly and inhibit viral replication. Specifically, we provide evidence that a 25-amino-acid peptide corresponding to the PA-binding domain of PB1 blocks the polymerase activity of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
145
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 21 publications
7
145
0
Order By: Relevance
“…To determine the role of cyclin T1/CDK9 in replication, we asked if cyclin T1/CDK9 was involved in regulating viral transcription. An influenza A virus minireplicon assay was employed to measure viral polymerase activity (10). Using this assay, we found that overexpression of either wild-type CDK9 or the dominant negative form of CDK9 (CDK9-DN) (29) did not affect viral transcription activity, while overexpression of cyclin T1 promoted the transcription activity of vRNP significantly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the role of cyclin T1/CDK9 in replication, we asked if cyclin T1/CDK9 was involved in regulating viral transcription. An influenza A virus minireplicon assay was employed to measure viral polymerase activity (10). Using this assay, we found that overexpression of either wild-type CDK9 or the dominant negative form of CDK9 (CDK9-DN) (29) did not affect viral transcription activity, while overexpression of cyclin T1 promoted the transcription activity of vRNP significantly (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work where a point mutation was introduced at amino acid 66 of PB1-F2 revealed the importance of this protein in the virulence of a H5N1 virus and the 1918 pandemic virus (37). A better understanding of the contribution of polymerase proteins in virulence will aid in designing drugs that target the key intersubunit binding sites of the polymerase complex and diminish the high replication efficiency of pandemic virus strains (39). For currently circulating H5N1 influenza viruses, the PB2 polymerase subunit appears to play a greater role in the high growth phenotype and increased virulence associated with these highly pathogenic viruses in mammals (40,41).…”
Section: Construction and Characterization Of Recombinant Viruses Witmentioning
confidence: 99%
“…Some of these interactions have been verified by co-crystallisation [55][56][57] and functional studies. 58 Also, some additional PB2-PA and PB1-PB2 interactions have been described in reference 40 and 59, that may play structural and/or regulatory roles in the activity of the viral polymerase.…”
Section: The Polymerase Complexmentioning
confidence: 99%